1987
DOI: 10.1111/j.1469-8137.1987.tb00168.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF MANGANESE ON ROOT EXTENSION OF GEUM RIVALE L., G. URBANUM L. AND THEIR HYBRIDS

Abstract: SUMMARYRoot elongation of Geum rivale and G. urbanum grown in nutrient solution decreased as manganese concentration was increased above 25 mg dm"^, especially in G. urbanum. Prior exposure of roots to 25 mg Mn dm~^ increased their capacity for subsequent elongation in manganese solutions, the effect of such pretreatment being most pronounced in G. rivale. G. rivale was significantly more tolerant of 50 mg Mn dm"^ than G. urbanum. Efflux of potassium from root segments, used as a measure of niembrane permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…However, the pattern of variation even within the small Highfolds area was for hybrids to intergrade with G. rivale. Experimental evidence has shown that progeny of hybrids raised as families do not necessarily have ecological tolerances intermediate between the parent species, and that these tolerances could not be consistently related to gross morphology (Waldren, Davies & Etherington, 1987b;Waldren, Etherington & Davies, 1988). Anderson (1949) suggested that genes which determine ecological preferences are inherited in the same way as morphological genes, but this does not necessarily mean that ecological and morphological genes will be inherited together because of linkage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pattern of variation even within the small Highfolds area was for hybrids to intergrade with G. rivale. Experimental evidence has shown that progeny of hybrids raised as families do not necessarily have ecological tolerances intermediate between the parent species, and that these tolerances could not be consistently related to gross morphology (Waldren, Davies & Etherington, 1987b;Waldren, Etherington & Davies, 1988). Anderson (1949) suggested that genes which determine ecological preferences are inherited in the same way as morphological genes, but this does not necessarily mean that ecological and morphological genes will be inherited together because of linkage.…”
Section: Discussionmentioning
confidence: 99%
“…A squared Euclidean distance dissimilarity matrix was calculated from standardized data and used for cluster analysis by Ward's error sum of squares method (Ward, 1963), using the CLUSTAN package (Wishart, 1978). Hybrid indices were calculated by the method of Waldren, Davies & Etherington (1987b), and ranged from 0 (G. urbanum) to 30 (G. rivale).…”
Section: Morphological Measurementsmentioning
confidence: 99%
“…Thus, a further possible reason for failing to detect F2s in the hybrid swarm is the lack of discriminatory power based on the genetic markers available. It is interesting to note that in previous studies of Geum hybrid swarms, individuals have been found resembling G. urbanum morphologically but displaying tolerance of waterlogging and manganese, adaptive characters normally associated with G. rivale (Waldren et al, 1987(Waldren et al, , 1988. Such individuals could represent inbreeding lines derived from F1s carrying limited genetic contributions from G. rivale, which confer adaptation to waterlogged conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Low oxygen availability reduces respiration and growth in nonadapted roots (Laan et al, 1990(Laan et al, , 1991 and can eventually lead to the death of root meristems. Some microorganisms use electron acceptors other than oxygen for respiration under these conditions (Laanbroek, 1990), resulting in the formation of potentially phytotoxic metal ions such as Fe# + (Ponnamperuma, 1972 ;Laan et al, 1989b) and Mn# + (Ponnamperuma, 1972 ;Waldren et al, 1987), and anions like sulphide (Lamers et al, *Author for correspondence (tel j31 24 3653382 ; fax j31 24 3652409 ; e-mail ericv!sci.kun.nl). 1998).…”
Section: mentioning
confidence: 99%